Complicated Inequality

Algebra Level 5

cyc ( x y ) 2 x + y k cyc ( x y ) 2 x + y 3 \displaystyle \sum_{\text{cyc}} \dfrac{(x-y)^2}{x+y} \geq \sqrt[3]{k \displaystyle \prod_{\text{cyc}} \dfrac{(x-y)^2}{x+y}}

Let x x , y y , z z be non-negative real numbers such that x y + y z + z x 0 xy+yz+zx\neq 0 . If the maximum value of k k such that the above inequality always holds true can be represented as a b a \sqrt{b} , where a a and b b are positive integers, and b b is square free, find a + b a+b .


The answer is 27.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
May 7, 2017

Reorganising the inequality, we want to find the largest k k such that [ ( x y ) 2 ( x + z ) ( y + z ) + ( x z ) 2 ( x + y ) ( y + z ) + ( y z ) 2 ( x + y ) ( x + z ) ] 3 k ( x + y ) 2 ( x + z ) 2 ( y + z ) 2 ( x y ) 2 ( x z ) 2 ( y z ) 2 = k ( x 2 y 2 ) 2 ( x 2 z 2 ) 2 ( y 2 z 2 ) 2 \Big[(x-y)^2(x+z)(y+z) + (x-z)^2(x+y)(y+z) + (y-z)^2(x+y)(x+z)\Big]^3 \; \ge \; k(x+y)^2(x+z)^2(y+z)^2(x-y)^2(x-z)^2(y-z)^2 \; = \; k(x^2 - y^2)^2(x^2 - z^2)^2(y^2-z^2)^2 for x , y , z 0 x,y,z \ge 0 with x y + x z + y z 0 xy + xz + yz \neq 0 , and so such that F ( x , y , z ) = [ ( x y ) 2 ( x + z ) ( y + z ) + ( x z ) 2 ( x + y ) ( y + z ) + ( y z ) 2 ( x + y ) ( x + z ) ] 3 ( x 2 y 2 ) 2 ( x 2 z 2 ) 2 ( y 2 z 2 ) 2 k F(x,y,z) \; = \; \frac{\big[(x-y)^2(x+z)(y+z) + (x-z)^2(x+y)(y+z) + (y-z)^2(x+y)(x+z)\big]^3}{(x^2 - y^2)^2(x^2 - z^2)^2(y^2-z^2)^2} \; \ge \; k for x , y , z 0 x,y,z \ge 0 with x y + x z + y z 0 xy + xz + yz \neq 0 and x , y , z x,y,z distinct. Since F ( x , y , z ) F(x,y,z) is a symmetric function of x , y , z x,y,z , we want to find the largest possible k k such that F ( x , y , z ) k 0 z < y < x F(x,y,z) \; \ge \; k \hspace{2cm} 0 \le z < y < x (the condition that x y + x z + y z 0 xy + xz + yz \neq 0 simply requires that at least two of x , y , z x,y,z are nonzero). Since F ( x , y , z ) F(x,y,z) is homogeneous of degree 0 0 , we may as well assume that z = 1 z=1 , and we want to find the largest possible k 0 k \ge 0 such that G ( x , y ) k G(x,y) \ge k for 0 x < y < 1 0 \le x < y < 1 , where G ( x , y ) = F ( x , y , 1 ) = [ ( x y ) 2 ( x + 1 ) ( y + 1 ) + ( x 1 ) 2 ( x + y ) ( y + 1 ) + ( y 1 ) 2 ( x + y ) ( x + 1 ) ] 3 ( x 2 y 2 ) 2 ( x 2 1 ) 2 ( y 2 1 ) 2 G(x,y) \; = \; F(x,y,1) \;= \; \frac{\big[(x-y)^2(x+1)(y+1) + (x-1)^2(x+y)(y+1) + (y-1)^2(x+y)(x+1)\big]^3}{(x^2-y^2)^2(x^2-1)^2(y^2-1)^2} In other words, k k is to be the minimum of G G over this domain. Looking for turning points of G ( x , y ) G(x,y) , we find that G x = 8 P ( x , y ) 2 ( x 2 1 ) 3 ( x 2 y 2 ) 3 ( y 2 1 ) 2 Q ( x , y ) G y = 8 P ( x , y ) 2 ( x 2 1 ) 2 ( x 2 y 2 ) 3 ( y 2 1 ) 3 Q ( y , x ) \frac{\partial G}{\partial x} \; = \; \frac{8P(x,y)^2}{(x^2 - 1)^3(x^2 - y^2)^3(y^2-1)^2}Q(x,y) \hspace{2cm} \frac{\partial G}{\partial y} \; = \; -\frac{8P(x,y)^2}{(x^2 - 1)^2(x^2 - y^2)^3(y^2 - 1)^3}Q(y,x) where P ( x , y ) = x 3 y + x y 3 + x 3 2 x 2 y 2 x y 2 + y 3 2 x y + x + y = ( 1 + x + y ) ( x y ) 2 + ( 1 x y ) [ x ( 1 x ) + y ( 1 y ) ] Q ( x , y ) = x 6 y 10 x 4 y 3 + x 2 y 5 + x 6 + 4 x 5 y + 5 x 4 y 2 4 x 3 y 3 2 x 2 y 4 + 4 x y 5 + 5 x 4 y + 8 x 2 y 3 + 3 y 5 10 x 4 4 x 3 y + 8 x 2 y 2 4 x y 3 6 y 4 2 x 2 y 6 y 3 + x 2 + 4 x y + 3 y 2 \begin{aligned} \ P(x,y) & = x^3y + xy^3 + x^3 - 2x^2y - 2xy^2 + y^3 - 2xy + x + y \\ & = (1+x+y)(x-y)^2 + (1-xy)\big[x(1-x) + y(1-y)\big] \\ Q(x,y) & = \begin{array}{l} x^6y - 10x^4y^3 + x^2y^5 + x^6 + 4x^5y + 5x^4y^2 - 4x^3y^3 - 2x^2y^4 + 4xy^5 + 5x^4y + 8x^2y^3 + 3y^5 \\ - 10x^4 - 4x^3y + 8x^2y^2 - 4xy^3 - 6y^4 - 2x^2y - 6y^3 + x^2 + 4xy + 3y^2 \end{array} \end{aligned} Thus solutions of the equation G = 0 \nabla G = \mathbf{0} are obtained either by solving P ( x , y ) = 0 P(x,y) = 0 or else Q ( x , y ) = Q ( y , x ) = 0 Q(x,y) = Q(y,x) = 0 . It is clear that the only solutions to the equation P ( x , y ) = 0 P(x,y) = 0 for 0 x , y 1 0 \le x,y \le 1 are x = y = 0 x=y=0 and x = y = 1 x=y=1 .

We note that we can write Q ( x , y ) + Q ( y , x ) = ( x + y ) R ( x , y ) Q ( x , y ) Q ( y , x ) = ( x y ) S ( x , y ) Q(x,y) + Q(y,x) \; = \; (x+y)R(x,y) \hspace{2cm} Q(x,y) - Q(y,x) \; = \; (x-y)S(x,y) for polynomials R ( x , y ) R(x,y) , S ( x , y ) S(x,y) .

Suppose that ( G ) ( x , y ) = 0 (\nabla G)(x,y) = \mathbf{0} for 0 x , y 1 0 \le x,y \le 1 but that P ( x , y ) 0 P(x,y) \neq 0 . This means that Q ( x , y ) = Q ( y , x ) = 0 Q(x,y) = Q(y,x) = 0 , and hence ( x + y ) R ( x , y ) = ( x y ) S ( x , y ) = 0 (x+y)R(x,y) = (x-y)S(x,y) = 0 . If x = y x=y , this means that either x = y = 0 x=y=0 or else R ( x , x ) = 0 R(x,x) = 0 . But R ( x , x ) = 8 ( x 1 ) 3 x ( 1 + x ) 2 R(x,x) = -8 (x-1)^3 x (1 + x)^2 , and hence either x = y = 0 x=y=0 or x = y = 1 x=y=1 . These cases can be ignored (since they imply that P ( x , y ) = 0 P(x,y) = 0 ). Thus we deduce that x y x \neq y , and hence that R ( x , y ) = S ( x , y ) = 0 R(x,y) = S(x,y) = 0 . The following graph, plotting R ( x , y ) = 0 R(x,y) = 0 (blue) and S ( x , y ) = 0 S(x,y) = 0 (orange) show that the only points where R ( x , y ) = S ( x , y ) = 0 R(x,y) = S(x,y) = 0 simultaneously for 0 x , y 1 0 \le x,y \le 1 are x = y = 0 x=y=0 and x = y = 1 x=y=1 . In other words, there are no solutions of ( G ) ( x , y ) = 0 (\nabla G)(x,y) = \mathbf{0} for 0 x , y 1 0 \le x,y \le 1 and x y x \neq y .

Mathematica backs this up, and tells me that the only solutions to the equations R ( x , y ) = S ( x , y ) = 0 R(x,y) = S(x,y) = 0 for 1 x , y 1 -1 \le x,y \le 1 are x = y = 0 x=y=0 and x = y = 1 x=y=1 . What I have not obtained is an algebraic proof of this, and would welcome any suggestions.

Thus we deduce that there are no turning points for the function G G in the domain 0 x < y < 1 0 \le x < y < 1 . Since G ( x , y ) G(x,y) \to \infty either as y 1 y \to 1 or as y x 0 y-x \to 0 , we deduce that the minimum for G G on this domain must be achieved on the boundary x = 0 x=0 . Thus, to minimize G ( x , y ) G(x,y) for 0 < x < y 1 0 < x < y \le 1 , we need simply to minimize G ( 0 , y ) = 8 ( y 2 + 1 ) 3 y ( y 2 1 ) 2 0 < y 1 G(0,y) \; = \; \frac{8 (y^2 + 1)^3}{y (y^2-1)^2} \hspace{2cm} 0 < y \le 1 The minimum is achieved at y = 3 2 y = \sqrt{3} - \sqrt{2} , and G ( 0 , 3 2 ) = 24 3 G\big(0,\sqrt{3}-\sqrt{2}\big) = 24\sqrt{3} .

Thus we deduce that k = 24 3 k = 24\sqrt{3} .

I suspect that it is possible, for any 0 x , y 1 0 \le x,y \le 1 , to find 0 v 1 0 \le v \le 1 such that G ( x , y ) G ( 0 , v ) G(x,y) \ge G(0,v) can be proved easily. If v v does exist, and an explicit form for this v v can be found, the whole business would be much simpler!

i had the same idea. but guessed things. is there a way to solve this without using calculus. i assume that x,y,z are non-negative and x+y+z=1. the inequality reduces to f(x,y,z)<=k. Here i had some idea. if we can prove that for fixed values of y,z. h(x)=f(x,y,z) is a convex function. then clearly the maximum value is attained at the boundary points. i did not prove this fact but assumed it and got the correct answer. thanks for the graph. it gives a clear idea how the function grows. Nice solution.

Srikanth Tupurani - 1 year, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...